2014
DOI: 10.1071/is13057
|View full text |Cite
|
Sign up to set email alerts
|

The first phylogenetic analysis of Palpigradi (Arachnida) – the most enigmatic arthropod order

Abstract: Palpigradi are a poorly understood group of delicate arachnids, often found in caves or other subterranean habitats. Concomitantly, they have been neglected from a phylogenetic point of view. Here we present the first molecular phylogeny of palpigrades based on specimens collected in different subterranean habitats, both endogean (soil) and hypogean (caves), from Australia, Africa, Europe, South America and North America. Analyses of two nuclear ribosomal genes and COI under an array of methods and homology sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Furthermore, there is a general paucity of information on the phylogenetic relationships within smaller arachnid orders. For example, just one molecular phylogenetic study of Palpigradi has been published to date ( Giribet et al, 2014 ). In Amblypygi, limited morphological phylogenies have been published ( Weygoldt, 1996 , Garwood et al, 2017 ) and no molecular phylogenetic study of the order as a whole has ever been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a general paucity of information on the phylogenetic relationships within smaller arachnid orders. For example, just one molecular phylogenetic study of Palpigradi has been published to date ( Giribet et al, 2014 ). In Amblypygi, limited morphological phylogenies have been published ( Weygoldt, 1996 , Garwood et al, 2017 ) and no molecular phylogenetic study of the order as a whole has ever been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Direct optimization analyses were conducted under the parsimony criterion in POY v.5.1.1 (Wheeler et al ., ) under a selection of six parameter sets, as in earlier studies (e.g. Giribet et al ., ). For the individual partitions, timed searches of 1 h were run on six processors.…”
Section: Methodsmentioning
confidence: 97%
“…Palpigrades are a poorly-known and obscure arachnid order (Harvey et al 2006). They are regarded as the most enigmatic arachnids and as one of the rarest and smallest groups among all terrestrial arthropods (Giribet et al 2014). First reported by Grassi & Calandruccio (1885) in the late 19 th century, no photos of living specimens were published before the beginning of the 21 st century (Kováč et al 2002) and their extraordinary feeding habit was revealed even later (Smrž et al 2013).…”
mentioning
confidence: 99%